2020
DOI: 10.1590/1808-1657001082018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hygienic-sanitary conditions of a dairy localized in the Island of São Luís, Maranhão

Abstract: The product quality is a competitive advantage that plays a differential role among companies. In the food industry, which is based on the Quality Management System, such as Good Manufacturing Practices (GMP), which cover the hygiene procedure, aiming at food safety. In view of the above, the aim of this study was to evaluate the hygienic-sanitary conditions of a selected dairy from the São Luís Island - MA. An application of the checklist was performed, swab collection from the hands of the manipulators and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
2
0
0
Order By: Relevance
“…The values of total coliforms varied from <0.3 to 2.3 MLN/mL and from < 0.3 to 1.5 MLN/mL for thermotolerant coliforms. Such data corroborate those found by Candeira et al (2020) and Figueiredo et al (2016), who found satisfactory results for workers' hands in a dairy farm in the state of Pará. Concerning equipment and utensils, all dairies in this study are within the standards.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The values of total coliforms varied from <0.3 to 2.3 MLN/mL and from < 0.3 to 1.5 MLN/mL for thermotolerant coliforms. Such data corroborate those found by Candeira et al (2020) and Figueiredo et al (2016), who found satisfactory results for workers' hands in a dairy farm in the state of Pará. Concerning equipment and utensils, all dairies in this study are within the standards.…”
Section: Resultssupporting
confidence: 90%
“…Values varied from <0.3 to 24 for total coliforms and thermotolerant, corroborating Candeira et al (2020), who found satisfactory results while evaluating a dairy farm's equipment.…”
Section: Resultssupporting
confidence: 78%